Sonographic Findings of Medullary Thyroid Carcinoma Leading to Diagnosis of Multiple Endocrine Neoplasia Type 2a during Pregnancy - Sherer, David M.; Dalloul, Mudar; Salame, Ghadir; Shah, Tana; Serur, Eli; Zinn, Harry L.; Abulafia, Ovadia (American Journal of Perinatology Reports, 2011)
Multiple endocrine neoplasia (MEN) type 2a (Sipple's syndrome) is characterized by medullary thyroid carcinoma and pheochromocytoma, and in a smaller percentage of cases, multiglandular parathyroid hyperplasia. This autosomal-dominant syndrome is due to a mutation in the rearranged during transfection (RET) proto-oncogene located on chromosome 10cen–10q11.2 and rarely complicates pregnancy. We present an unusual case in a patient with an enlarged thyroid with sonographic findings characteristic of thyroid cancer, which led to diagnosis and subsequent management of RET proto-oncogene-positive MEN type 2a complicating pregnancy.
Keywords: Pregnancy; ultrasound; thyroid carcinoma; pheochromocytoma; multiple endocrine neoplasia type 2a